Предмет: Математика,
автор: tyrewer4747
решите уравнение 3у + 0,5(2 - (6у - 8)) - 5((2 - 7у) - 11) - 49 + 6(2- 3у) = -4
Пажалуйста заметьте , Срочно решите.
Ответы
Автор ответа:
1
Ответ:
у=-1
Пошаговое объяснение:
3у+0,5(2-6у+8)-5(2-7у-11)-49+12-18у=-4
3у+1-3у+4-10+35у+55-49+12-18у=-4
35у-18у=-4-1-4+10-55+49-12
17у=-76+59
17у=-17
у=-1
tyrewer4747:
спасибо
Похожие вопросы
Предмет: Английский язык,
автор: karamelka0906
Предмет: Математика,
автор: Аноним
Предмет: Математика,
автор: amina211
Предмет: Литература,
автор: NikitaGerek
Предмет: Математика,
автор: Polinapom